POTENTIAL OF Moringa oleifera SEED COAGULANT FOR ABATTOIR WATEWATER TREATMENT - GARBA YUSUF, YUSUF; MOHAMMED, SULAIMAN; MUHAMMAD, ISA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Abattoir is one of the factories that is becoming environmental threat in the urban cities due to the amount of wastewater generated. In the process of operation, huge volume of effluent is released directly to the environment. Moringa oleifera seeds serves as natural coagulant and reported to be use for treatment of wastewater. In the present study, discharged abattoir wastewater was collected from Potiskum main abattoir and treat with the natural coagulant. 2.5 g of Moringa oleifera seed powdered was dissolved into 50mL distilled water, then blend at high speed to extract the active coagulant agent. The seeds extract solution 25ml, 30ml and 35ml was transferred into 450ml of the wastewater for coagulation by jar test experiment. The results indicated that majority of the tested physicochemical parameters were high alarming to maximum effluent. Subsequent to the treatment, turbidity removal of 72.17, TSS 73.90, conductivity 56.45, TDS 21.97, while pH was adjusted between 7.0 - 7.5 was obtained. The results have shown that abattoir wastewater treated with Moringa oleifera seed coagulant is effective in reducing the determined physicochemical parameters. The result demostrate that Moringa oleifera seed has represents a powerful option for usage as natural plant material for abattoir wastewater treatment.